Self-processing characteristics from first-person and third-person perspectives in individuals with social anxiety disorder: insights into negative bias - Wu, Huating; Yue, Caizhen; Cao, Fasheng; Long, Yihong; Wang, Yan (Frontiers in Psychiatry, 2024)
As one of the most common psychological problems, social anxiety disorder (SAD) has lots of negative effects on the physical and mental development of individuals, such as decreasing the quality of interpersonal relationships, and even causing depression, suicidal ideation, etc., as well as leads individuals to generate mental illness stigma. The mental illness stigma that individuals perceive not only affects how they perceive themselves (first-person perspective), but also how they perceive others' appraisals of them (third-person perspective), which further exacerbate their anxiety symptoms. This study adopted the self-referential paradigm to explore the self-processing characteristics of individuals with social anxiety disorder from the firstperson perspective and the third-person perspective. 30 individuals with social anxiety disorder were selected as the experimental group in Experiment 1, and the results showed that the recognition rate of individuals with social anxiety disorder under the self-appraisals condition was significantly higher than that under the condition of appraisals on mothers; In the three conditions of self-appraisals, appraisals on mothers and mothers' reflected appraisals, the recognition rate of negative trait adjectives was significantly higher than that of positive trait adjectives. In Experiment 2, 31 individuals without social anxiety disorder were selected as the control group, and the results showed that there was no significant difference in recognition rate under the three conditions, and the recognition rate of positive trait adjectives was significantly higher than that of negative trait adjectives under the three conditions. This study indicates that individuals with social anxiety disorder have the negative bias in self-processing and are more likely to focus on self-information, which is different from the self-positive bias of individuals without social anxiety disorder. This study can be beneficial to know the self-cognitive characteristics of individuals with social anxiety disorder, help them get rid of negative cognitive patterns, and remove the mental illness stigma.